Estudio de caracterización de residuos sólidos de la ciudad de Soritor - Ruiz Arbildo, Emerson (2014)
This research project entitled: CHARACTERIZATION STUDY OF SOLIO WASTE IN THE Soritor District 2012, has been performed in arder to favor the urban development and presentation as a city of healthy, likewise help improve waste management city solids Soritor; such as by making an appropriate selection on the Physical Characterizatlon different generation sources. The salid waste management involves the generation, storage, collection, transportation and disposal of salid waste; if these wastes are not properly treated, as you might know whether the appearance of arder, cleanliness and beautification improve or, if we are destroying garbage in the streets and public places, which, without thinking, we would be damaging the ornament of the city and the quality of lite for residents. 8oth in the past, as now happens in some developing countries, there are people who coexist with "urban mountains of garbage", in rodents roaming bands of semidomestic dogs and other animals, studies of this project, projected that 70% of the population is satisfied with the collection service, but not with the service they waste disposal; beca use it would, lack coordination in the frequency of these residues. lt is noteworthy that the waste can be generated by different sources, this yields a PPC in the city of Soritor of 0.65 kg 1 capita 1 day, the component with the highest percentage of organic matter. The District Municipality of Soritor should restructure the new functional organization to improve the management of salid waste; Also, make a work of community relations to salve possible conflicts in their commune.